Pengembangan E-Modul Berbasis Microsite Terhadap Kemampuan Representasi Matematis Siswa pada Materi Statistika - Annisah, Vera; Nurmaningsih, Nurmaningsih; Oktaviana, Dwi (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to develop learning media in the form of microsite-based e-modules designed for students' mathematical representation abilities in statistical materials in grade VIII of SMP Negeri 5 Sungai Kakap. This research uses a research and development (R&D) approach by adapting the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The subjects in this study involve validators (material experts and media experts) and grade VIII students as product users in the trial. The data collection technique is carried out through indirect communication using instruments in the form of expert validation sheets and teacher and student response questionnaires. The results of validation by material experts showed a validity rate of 87.82% which was included in the very valid category. Validation by media experts obtained a score of 95.90% which is also considered very valid. Meanwhile, the practicality of the product based on teacher responses reached 96.67% and student responses of 91.25%, both of which are included in the very practical category. The effectiveness test through posttest results showed a percentage of 75.867% which was included in the effective category. These findings show that microsite-based e-modules are suitable for use as digital-based learning teaching materials to support the improvement of students' mathematical representation skills.